电子节气门控制策略研究 - 郭辉; 张振东; 朱红萍 (Jixie chuandong)
The structure and the principle of the electronic throttle control system（ETCS） are described,and the nonlinearity is analyzed.According to the mathematical model of ETCS,three controllers are designed and simulated.The results indicate that the PID controller is easy to realize,but has an overshoot;the Fuzzy controller can better follow the control objectives,but has hysteresis;and the sliding mode controller has better robustness,and can be used to control ETCS.